What Information Needed to Present in a Fundraising Campaign through Equity Crowdfunding - Fajarini, Chika; Dalimunthe, Zuliani; Haikal, Shalahuddin (UI Scholars Hub, 2021)
This study aims to determine success factors on equity-based crowdfunding project fundraising in several countries in Asia. We evaluated three categories of factors: campaign characteristics, human capital factors, and social capital factors. We evaluate models using 201 project samples on various platforms from Indonesia, Malaysia, United Arab Emirates, Israel, and South Korea from January 2018 until December 2019. We used Ordinary Least Square (OLS) as the method of hypothesis testing. We found that the most critical variable in the campaign characteristics is the financial information provided. Meanwhile, unless the number of team members, each human capital factor significantly positive to campaign success. Lastly, both social networks and business advisor's presence have a significant positive relationship to crowdfunding project fundraising success. However, we do not found a significantly different pattern between high-income and lower-income countries evaluated.